Ethnobotanical study on plants used to dye traditional costumes by the Baiku Yao nationality of China - Renchuan Hu; Tingting Li; Yunrui Qin; Yujing Liu; Yunfeng Huang (BMC, 2022)
Abstract Background The Baiku Yao is a branch of the Yao nationality in China. The unique dying process of traditional clothing employed by these people has distinct national characteristics, a profound impact on the production and life of local people, and important research value. For this reason, it is important to investigate and document the dyeing plants and the traditional knowledge involved in the dyeing of Baku Yao traditional clothing. Methodology Information on dyeing plants was obtained using the free-list method and interviews with 61 Baiku Yao informants in Guangxi and Guizhou from January 2020 to August 2021. Based on the free-list method, we evaluated and screened out important plants by calculating the cognitive salience value of each plant. Results The results showed that the people of Baiku Yao have accumulated rich traditional knowledge of dyeing plants and long-term dyeing and other processes. We collected 23 species and recorded the related traditional knowledge, such as the Baiku Yao name, life form, habitat, part(s) used, application type, usage, and area used. The utilization of dyeing plants has a strong relationship with ethnic culture. The Baiku Yao uses unique anti-dyeing material (Ailanthus vilmoriniana) in the cotton dyeing process, they call it "the mother tree". As well as, the results also showed that 15 plants (65.2%) have medicinal value and can be used to treat 18 aliments, and wild plants play a very important role in the life of the Baiku Yao. Conclusion These plants not only meet the color needs of the Baiku Yao people but also have health care effects, aligning with the trends toward green dyeing and the health contentiousness of modern people. This study provides a reference for the inheritance and development of Baiku Yao traditional clothing dyeing culture, will aid the identification of new natural, safe and healthy textile dyes, and is of positive significance in promoting regional economic development, national cultural inheritance, and biodiversity protection.